2007
DOI: 10.1128/jcm.00794-07
|View full text |Cite
|
Sign up to set email alerts
|

Capsule Gene Analysis of Invasive Haemophilus influenzae : Accuracy of Serotyping and Prevalence of IS 1016 among Nontypeable Isolates

Abstract: We evaluated the accuracy of serologic capsule typing by analyzing capsule genes and related markers among invasive Haemophilus influenzae isolates before and after the introduction of H. influenzae serotype b (Hib) conjugate vaccines. Three hundred and sixty invasive H. influenzae isolates were collected as part of Active Bacterial Core surveillance within the Georgia Emerging Infections Program between 1 January 1989 and 31 July 1998. All isolates were biotyped, serotyped by slide agglutination serotyping (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
55
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 56 publications
2
55
0
Order By: Relevance
“…Chromosomal DNA was extracted from 229 PCR-confirmed NTHI strains collected between August 1998 and December 2006 (9) and hybridized with digoxigenin-labeled pUO38 (39), pBR322 (8), or IS1016 as previously described (53).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chromosomal DNA was extracted from 229 PCR-confirmed NTHI strains collected between August 1998 and December 2006 (9) and hybridized with digoxigenin-labeled pUO38 (39), pBR322 (8), or IS1016 as previously described (53).…”
Section: Methodsmentioning
confidence: 99%
“…In division I encapsulated H. influenzae strains, the cap locus is flanked by direct repeats of the IS1016 insertion element; division II encapsulated H. influenzae strains contain one or more IS1016 elements that are unassociated with cap genes. A number of investigators have shown that while IS1016 elements are generally absent in NTHI, they may be present in a small (but varying) proportion of NTHI isolates from the respiratory tract and invasive disease (53,59,60). It has been suggested that the presence of IS1016 in NTHI may be a marker for a more recent evolution from encapsulated H. influenzae (59,60).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Region II carries serotype-specific biosynthesis genes unique to each of the six capsule types; the regions from representatives of each serotype have been sequenced and comprise three to eight genes (49,(55)(56)(57)(58). Assignment to serotypes may be done by slide agglutination or by PCR; however, slide agglutination carries a high rate of discordance compared with PCR-based methods (59)(60)(61)(62)(63).…”
Section: The Haemophilus Influenzae Groupmentioning
confidence: 99%
“…Agglutination with antisera is an alternative method used for capsular typing. Even though this is a faster method than PCR, studies have shown that its accuracy is comparatively poor (12).…”
mentioning
confidence: 99%